Governance and global collaboration in non‐democratic countries - Hamid E. Ali (22330765) (2024)
The concept of good governance (GG) has emerged from the corridors of global institutions, influencing changes, particularly in non‐democratic countries. This paper uses both qualitative and quantitative approaches to address the following question: To what extent does global collaboration (GC) impact governance in non‐democratic countries? The paper incorporates proxies for GC, more deeply exploring the dynamics and frameworks that link GC and governance. The GC variables measuring institutional globalization have a positive impact on governance, while global openness and information globalization have a negative impact. These mixed results invite further research on governance and GC. However, the national visions can set the stage for future agendas that combine partnership, collaboration, transparency, and innovation to achieve GG. Other Information Published in: Public Administration Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/puar.13897